Daytime Variation in Serum Progesterone During the Mid-Luteal Phase in Women Undergoing In Vitro Fertilization Treatment - Thomsen, Lise Haaber; Kesmodel, Ulrik Schiøler; Andersen, Claus Yding; Humaidan, Peter (Frontiers in Endocrinology, 2018)
Objective: To investigate whether mid-luteal serum progesterone (P4) exhibits significant fluctuations during a 12-hour daytime period in women undergoing in vitro fertilization (IVF) and to explore whether the extent of these fluctuations could impact the interpretation of luteal progesterone levels in a clinical setting. Design: Explorative pilot study Setting: Public hospital-based fertility unit. Patients: Ten women undergoing IVF treatment. Intervention: Seven days after oocyte pick-up, patients underwent frequent repeated blood sampling (every 60 minutes for 12 hours and during two of these hours, every 15 minutes). Serum samples were analyzed for progesterone, estradiol and LH. Main outcome Measures: Daytime fluctuations in s-progesterone and s-estradiol. Results: There was a significant positive correlation between median P4 levels and the magnitude of P4 variations – women with median P4 < 60 nmol/l had clinically stable P4 levels throughout the day, while patients with median P4 > 250 nmol/l exhibited periodic P4 peaks of several hundred nmol/l. These endogenous P4 fluctuations were observed irrespective of the type of stimulation protocol or mode of triggering of final oocyte maturation. Simultaneously large fluctuations were seen in s-estradiol. Conclusion: Monitoring of early to mid-luteal P4 levels in IVF-cycles may be valuable in the planning of individualized luteal phase support in the attempt to increase reproductive outcomes. The prerequisite for luteal phase monitoring is, however, that the validity of a single measured P4 value is reliable. We show for the first time, that a single P4-measurement in the low progesterone patient quite accurately reflects the corpus luteum function and that the measurement can be used to detect IVF patients with a need of additional exogenous luteal P4 administration.